Detecção de Neospora caninum, Sarcocystis neurona e Toxoplasma gondii em bovinos - Roman, Isac Junior (2024)
The phylum Apicomplexa is a large group of parasitic protists. Cattle can be affected by single or mixed infections simultaneously, involving more than one genus, and sometimes multiple species of apicomplexans, such as: Sarcocystis spp., Neospora caninum, Toxoplasma gondii. Apicomplexan infections in cattle have direct and indirect implications; direct ones relate to bovine health, while indirect ones are important for biosecurity. Therefore, this thesis aims to address the infection of Neospora caninum, Toxoplasma gondii, and Sarcocystis neurona in samples obtained from cattle. In the first study, the objective was to determine the frequency of detecting anti-N. caninum antibodies in three different sample types and sampling methods: a prevalence study, routine diagnostic laboratory samples, and bovine fetal serum samples. These samples were collected from cattle in Rio Grande do Sul (RS), Brazil, and analyzed using the indirect immunofluorescence technique. The prevalence of N. caninum in the RS state was 22.8% (285/1248). In routine diagnostic samples, an average antibody detection rate of 29.95% (985/3289) for anti-N. caninum was found. In bovine fetal serum samples, there was a detection rate of 35% (35/100). The second article aimed to describe the molecular detection of Sarcocystis neurona, Toxoplasma gondii, and Neospora caninum in brain samples obtained from bovine fetuses at a slaughterhouse in southern Brazil. Brain samples from 35 clinically asymptomatic pregnant cow fetuses were screened using polymerase chain reaction (PCR) to amplify a fragment of the conserved 18S rRNA gene among apicomplexans. The amplicons underwent a digestion process using restriction enzymes to distinguish between the apicomplexans. Of the 35 brain samples tested, 26 were positive in PCR for the 18S rRNA gene. Among these, 23 were digested with restriction enzymes, resulting in 17 samples positive for S. neurona, five for N. caninum, and one for T. gondii. Specific primers for S. neurona, N. caninum, and T. gondii were used. DNA sequencing and phylogenetic analysis were performed on an amplified sample of S. neurona, which showed a nucleotide identity of 97.79% and clustered with S. neurona sequences available in GenBank. Our results confirm: i) infection of cattle by known apicomplexans like N. caninum, associated with reproductive disorders, ii) T. gondii considered non-pathogenic but of unique public health importance, and iii) demonstrate cattle susceptibility to apicomplexans not previously reported, as seen with S. neurona in this study. The data from this study underscore the need for further research to elucidate the importance of S. neurona and T. gondii infections in cattle, along with efforts aimed at controlling bovine neosporosis.